Learn to remember : train your brain for peak performance, discover untapped memory powers, develop instant recall, never forget names, faces and numbers - O'Brien, Dominic (Duncan Baird, 2009)
Where did you leave the car keys? What is the name of the new person in accounts? When is your partner's birthday? There are many times in the normal day when we rack our brains to remember simple things, now memory master Dominic O'Brien has the answer. Learn to Remember is a unique illustrated guide to enhancing your memory, featuring tried and tested practical techniques for combating forgetfulness. Whether you want to improve your memory at home, in your relationship, at work, or when you study, there is a technique in this guide to help you. With visualisation systems that can be customised to the individual, this really is a book that can help anyone remember better.